Gastrite atrófica do corpo: estudo das alterações histopatológicas da mucosa gástrica e relação com auto- imunidade e níveis séricos de gastrina - Carolinne Bahia Rodrigues (2007)
Atrophic body gastritis with antral mucosa relatively well preserved is frequently associated to hypergastrinemia and endocrine cell hyperplasia of the oxyntic mucosa. The histopathological diagnosis of autoimmune gastritis, mainly in its early stages, may be difficult to recognize. Various degrees of these lesions can also be seen in H. pylori multifocal gastritis. The present study was carried out to investigate the presence and the histological pattern of antral and body mucosa endocrine cell proliferation and its possible relationship with hypergastrinemia and autoimmunity. These criteria were evaluated in our series of 44 (10 male, 34 female) out of 194 dyspeptic patients submitted to gastroduodenal endoscopyand presenting body predominant atrophic gastritis, between april/2004 to march/2006 at the Instituto Alfa de Gastroenterologia, Hospital das Clínicas da UFMG, Belo Horizonte, Brasil. Assessment of serum parietal cell antibodies, gastrin-17 and cobalamin levels was performed.The population of parietal cells was simultaneously evaluated by H & E and immunohistochemical staining. Grimelius technique was used for demonstration of argyrophil cells of the antrum and gastric body. Endocrine cell hyperplasia was frequently seen in body mucosa (34cases, 77.3%) and less frequently in antral mucosa (8 cases, 18.2%). Serum gastrin range was 41.4 2,720 pg/ml (mean, 349.5 pg/ml). Parietal cells were completely absent in the samples of 24 (54.5%) patients and decreased in number in 16 (36.3%) patients. Parietalcell antibodies were present in 32 (72.7%) patients, 31 of them (96.8%) presented endocrine cell hyperplasia in body mucosa (p < 0, 0001). No relationship was noted between the levels of gastrinemia and the degree of endocrine cell proliferation. Our results indicate that the diagnosis of autoimmune atrophic gastritis may be suspected microscopically in endoscopic specimens of the gastric mucosa when the routine histopathological features are combined with the histochemical detection of ECL hyperplasia.